Morphological evidence for azimuthal variations of the cosmic ray ion acceleration at the blast wave of SN 1006 - Cassam Chenaï, Gamil (2008)
Using radio, X-ray and optical observations, we present evidence for morphological changes due to efficient cosmic ray ion acceleration in the structure of the southeastern region of the supernova remnant SN 1006. SN 1006 has an apparent bipolar morphology in both the radio and high-energy X-ray synchrotron emission. In the optical, the shock front is clearly traced by a filament of Balmer emission in the southeast. This optical emission enables us to trace the location of the blast wave (BW) even in places where the synchrotron emission from relativistic electrons is either absent or too weak to detect. The contact discontinuity (CD) is traced using images in the low-energy X-rays (oxygen band) which we argue reveals the distribution of shocked ejecta. We interpret the azimuthal variations of the ratio of radii between the BW and CD plus the X-ray and radio synchrotron emission at the BW using CR-modified hydrodynamic models. We assumed different azimuthal profiles for the injection rate of particles into the acceleration process, magnetic field and level of turbulence. We found that the observations are consistent with a model in which these parameters are all azimuthally varying, being largest in the brightest regions.